2008
DOI: 10.1146/annurev.publhealth.29.091307.083824
|View full text |Cite
|
Sign up to set email alerts
|

The Value and Challenges of Participatory Research: Strengthening Its Practice

Abstract: The increasing use of participatory research (PR) approaches to address pressing public health issues reflects PR's potential for bridging gaps between research and practice, addressing social and environmental justice and enabling people to gain control over determinants of their health. Our critical review of the PR literature culminates in the development of an integrative practice framework that features five essential domains and provides a structured process for developing and maintaining PR partnerships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
938
0
25

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 958 publications
(973 citation statements)
references
References 109 publications
(251 reference statements)
10
938
0
25
Order By: Relevance
“…3,[15][16][17][18] Briefly, these include: (1) helping ensure that the research question comes from, or is of genuine importance to, the local community; (2) increasing trust and credibility with the community, which can in turn improve participation in research; (3) enhancing the cultural acceptability of study instruments, often improving their validity; (4) improving the design and implementation of interventions, increasing the likelihood of success; (5) improving data interpretation; (6) identifying and using new channels for dissemination; (7) helping translate the findings into action that will benefit the community; and (8) building individual and community capacity and leaving behind a community better able to study and address other health and social issues of local concern. Each of these is illustrated in the case study below.…”
Section: Cbpr and Urban Immigrant Worker Health: What's The Value Added?mentioning
confidence: 99%
“…3,[15][16][17][18] Briefly, these include: (1) helping ensure that the research question comes from, or is of genuine importance to, the local community; (2) increasing trust and credibility with the community, which can in turn improve participation in research; (3) enhancing the cultural acceptability of study instruments, often improving their validity; (4) improving the design and implementation of interventions, increasing the likelihood of success; (5) improving data interpretation; (6) identifying and using new channels for dissemination; (7) helping translate the findings into action that will benefit the community; and (8) building individual and community capacity and leaving behind a community better able to study and address other health and social issues of local concern. Each of these is illustrated in the case study below.…”
Section: Cbpr and Urban Immigrant Worker Health: What's The Value Added?mentioning
confidence: 99%
“…The methodology is based on participative research, 7,10 as the authors were also involved with formulating and implementing the oral health monitoring policy and the SBBrasil 2010.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the tool requests identification of key knowledge translation strategiesa core component of the template -and refers to the current state of the evidence base for knowledge translation strategies (Boaz et al, 2011;Grol & Grimshaw, 2003). In addition, the tool captures plans and methods for integrated knowledge translation based on an extensive amount of academic literature that describes how the involvement of knowledge users in the research process will increase the uptake of research results and improve the relevance of research findings (Cargo & Mercer, 2008;CIHR, 2013;Israel et al, 1998;Lomas, 2000;Macaulay et al, 2011). In contrast to open call researchers working in all types of health research, a CIHR evaluation of their knowledge translation funding found that researchers involved in integrated knowledge translation were more likely to report influencing their study stakeholders, health system/care practitioners, patients and consumers of healthcare, healthcare managers, healthcare professional organizations, federal/provincial representatives, community/municipal organizations, as well as consumer groups and charitable organizations (CIHR, 2013).…”
Section: Melanie Barwickmentioning
confidence: 99%